RESPON PERTUMBUHAN DAN HASIL BAWANG MERAH TERHADAP KONSENTRASI AUKSIN PADA TANAH GAMBUT - haryandi, haryandi; Nurjani, Nurjani; Safwan, Mulyadi (Jurnal Sains Pertanian Equator, 2018)
This research aims to determine the effect and the best dose of Atonik ZPT use on the growth and yield of shallot plants on peatlands. The research was conducted in experimental garden of Faculty of Agriculture of Tanjungpura University from July to September 2017. This research used Completely Randomized Design (RAL) consisting of 5 treatments with 5 replications. Each replication consists of 4 plant samples, so the total number is 100 plants. The treatments were as follows: a1 = Atonic Concentration of 0.25 cc / liter, a2 = Atonic Concentration of 0.50 cc / liter, a3 = Atonic Concentration of 0.75 cc / liter, a4 = Atonic Concentration of 1, 00 cc / liter and a5 = Atonik Concentration of 1.25 cc / liter. Observation variables include: plant height, number of tubers per hill, fresh weight of tubers per hill, dry weight of tuber bulbs per hill and weight per unit of tubers. Based on the result of research that, giving of Atonik Concentration does not influence to plant height, number of tuber per hill, fresh weight of tuber per hill, dry weight of tuber bulb per hill and weight per unit of tuber.key word: shallot, Atonik Concentration, peatlands.